(untitled) (Bioresearch Communications, 2026)
The present study evaluated the efficacy of five chemical fungicides, viz., Capvit 50 WP, Knowin 50 WP, Ridomil Gold MZ 68, Thiovit 80 WG and Tilt 250 EC at 100, 200, 300, 400 and 500 ppm concentrations against pathogenic fungi of selected rice varieties BRRI dhan 90 to BRRI dhan 99. Pathogenic fungi were Aspergillus niger, Curvularia lunata, and Fusarium solani. In this study, out of five fungicides Tilt 250 EC showed the complete growth inhibition of above mentioned three pathogenic fungi at all the concentrations used. Knowin 50 WP completely inhibited radial growth of A. niger at all the concentration used. Knowin 50 WP, also showed 94.00 % inhibition of the radial growth of F. solani at 100 ppm concentration. The fungicide showed complete inhibition of F. solani at 200, 300, 400 and 500 ppm concentrations used. Bioresearch Commu. 12(2): 2109-2114, 2026 (January)